Physician Attitudes toward Adult Vaccines and other Preventive Practices, United States, 2012. (March 2016) - Hurley, Laura P.; Bridges, Carolyn B.; Harpaz, Rafael; Allison, Mandy A.; Leary, Sean T. O'; Crane, Lori A.; Brtnikova, Michaela; Stokley, Shannon; Beaty, Brenda L.; Jimenez-Zambrano, Andrea; Kempe, Allison
Objectives: We described the following among U.S. primary care physicians: ( 1 ) perceived importance of vaccines recommended by the Advisory Committee on Immunization Practices relative to U.S. Preventive Services Task Force (USPSTF) preventive services, ( 2 ) attitudes toward the U.S. adult immunization schedule, and ( 3 ) awareness and use of Medicare preventive service visits. Methods: We conducted an Internet and mail survey from March to June 2012 among national networks of general internists and family physicians. Results: We received responses from 352 of 445 (79%) general internists and 255 of 409 (62%) family physicians. For a 67-year-old hypothetical patient, 540/606 (89%, 95% confidence interval [CI] 87, 92) of physicians ranked seasonal influenza vaccine and 487/607 (80%, 95% CI 77, 83) ranked pneumococcal vaccine as very important, whereas 381/604 (63%, 95% CI 59, 67) ranked Tdap/Td vaccine and 288/607 (47%, 95% CI 43, 51) ranked herpes zoster vaccine as very important ( p <0.001). All Grade A USPSTF recommendations were considered more important than Tdap/Td and herpes zoster vaccines. For the hypothetical patient aged 30 years, the number and percentage of physicians who reported that the Tdap/Td vaccine (377/604; 62%, 95% CI 59, 66) is very important was greater than the number and percentage who reported that the seasonal influenza vaccine (263/605; 43%, 95% CI 40, 47) is very important ( p <0.001), and all Grade A and Grade B USPSTF recommendations were more often reported as very important than was any vaccine. A total of 172 of 587 physicians (29%) found aspects of the adult immunization schedule confusing. Among physicians aware of "Welcome to Medicare" and annual wellness visits, 492/514 (96%, 95% CI 94, 97) and 329/496 (66%, 95% CI 62, 70), respectively, reported having conducted fewer than 10 such visits in the previous month. Conclusions: Despite lack of prioritization of vaccines by ACIP, physicians are prioritizing some vaccines over others and ranking some vaccines below other preventive services. These attitudes and confusion about the immunization schedule may result in missed opportunities for vaccination. Medicare preventive visits are not being used widely despite offering a venue for delivery of preventive services, including vaccinations.